Etika Sosial Dan Harmonisasi Masyarakat: Kajian Tafsir Tematik Surah Al-Hujurat Ayat 9-13 - Elsa Alfaiza Rahmadani; Nayla Afita; Syarif Hidayah Tulloh; Samiun Alim; Edi Hermanto (CV. ITTC INDONESIA, 2026)
Social ethics is a crucial aspect of Islamic teachings, governing interpersonal relationships to create a peaceful, just, and harmonious society. Various social issues, such as conflict, hate speech, bullying, prejudice, and low respect for diversity, demonstrate the importance of strengthening social ethical values ​​in modern society. This study aims to examine the social ethical values ​​contained in Surah Al-Hujurat, verses 9–13, and analyze their relevance to achieving societal harmony. This study employed a qualitative method with library research. Data were obtained from the Quran, tafsir books, and various literature related to social ethics and social life. Data analysis was conducted descriptively and analytically, focusing on the content of the verses under study. The research results show that Surah Al-Hujurat, verses 9–13, contains comprehensive principles of social ethics, including just conflict resolution, strengthening brotherhood (ukhuwah), prohibiting insulting and criticizing others, prohibiting prejudice, gossiping, and backbiting, as well as respecting diversity through the concept of ta'aruf (religious dialogue). These values ​​are strongly relevant in facing various contemporary social challenges and can serve as a foundation for building a harmonious, inclusive, and civilized society.